Welding essentials questions & answers - Galvery, William L., Jr (Industrial Press, 2006)
From the Publisher: As a concise yet thorough introduction to the topic, this new edition of a bestseller makes welding easy for beginners and is a handy reference for professionals. Its unique, comprehensive question-and-answer format allows readers to quickly find what they are looking for and fully understand it. Eliminating non-essential items to prevent overloading readers, Welding Essentials addresses safety hazards and required precautions in detail and provides solutions to common problems for each process. Additionally, this valuable reference carefully explains step-by-step setup and shutdown procedures, along with why equipment grounding and GFI's are needed and the way in which they work.
Keywords: Welding -- Handbooks, manuals, etc.; elektronické knihy; electronic books